Здравствуй Удмуртия: справочное издание / сост.: Г. Г. Грязев, В. Ю. Семенов - Грязев Г. Г. (Удмуртия, 2016)
Экземпляры: ф.1 (20161020) / Инвентарный номер: 53145 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: З-46 / ББК: 63.3 (2Рос. Удм)